Associations between chronotype, sleep disturbances and seasonality with fatigue and inflammatory bowel disease symptoms. (3rd August 2018) - Chrobak, Adrian A.; Nowakowski, Jarosław; Zwolińska-Wcisło, Małgorzata; Cibor, Dorota; Przybylska-Feluś, Magdalena; Ochyra, Katarzyna; Rzeźnik, Monika; Dudek, Alicja; Arciszewska, Aleksandra; Siwek, Marcin; Dudek, Dominika
ABSTRACT: Growing number of studies suggests link between circadian rhythms and inflammatory bowel diseases (IBD) manifestation. We hypothesize that: 1) IBD are associated with increased eveningness and sleep disturbances; 2) eveningness and sleep disturbances are related to more severe IBD symptoms. In total, 129 participants were enrolled to this study, divided into three groups: 34 Crohn's disease (CD) patients, 38 ulcerative colitis (UC) patients and 57 healthy controls (HC) group. They all fulfilled a questionnaire, consisting of the Composite Scale of Morningness (CSM), Seasonal Pattern Assessment Questionnaire (SPAQ), Pittsburgh Sleep Quality Index, Inflammatory Bowel Disease Questionnaire (IBDQ) and Multidimensional Fatigue Inventory (MFI). Multiple regression models controlled for age and sex revealed that in CD group higher eveningness measured with CSM was associated with higher general fatigue, physical fatigue, mental fatigue and reduced motivation measured by MFI. Lower CSM morning affect is associated with greater general fatigue, physical fatigue and more reduced activity. Greater seasonality scores are associated with increased physical fatigue and more reduced activity and motivation. Lower sleep quality measured with PSQI is associated with higher physical fatigue and more reduced activity. Correlational analysis revealed that higher seasonality and lower sleep quality are associated with increased systemic and bowel symptoms and decreased emotional and social functions measured with IBDQ. In UC group, eveningness is associated with greater general fatigue, physical fatigue and more reduced activity. Higher CSM morning affect is associated with decreased general fatigue, physical fatigue and less reduced activity. Higher CSM circadian preference scores are associated with decreased general and physical fatigue, and less reduced activity. Increased seasonality is associated with more physical fatigue. Lower sleep quality is associated with greater general and physical fatigue. To our best knowledge this is the first study evaluating associations between chronotype and sleep disturbances with IBD symptoms. We have found that chronotype preferences, whose role in IBD has been until now overlooked, may be one of the important factors contributing to fatigue in this clinical group.